Perancangan Pondok Pesantren Modern Di Kabupaten Bekasi Dengan Pendekatan Arsitektur Neo Vernakular - Purnama Sakhrial Pradini; Aditya Nur Pratama (Prosiding Sains dan Teknologi, 2022)
As a country with the most Muslims in Indonesia and even in the world, it is not surprising that Indonesia has many centers of Islamic education. Even in the midst of this globalization era, Islamic education has never lost interest. The development is even more visible with the number of Islamic boarding schools increasing in number of devotees. Modern Islamic boarding schools are a combination of the curriculum of Islamic boarding schools with the national education curriculum. Islamic boarding schools which are also a form of educational forum in Indonesia should have graduation standards that also follow the development of education according to the national and even international education curriculum. Bekasi Regency is one of the largest industrial cities in Indonesia and is geographically close to the capital city, but the quality of education in Bekasi is still not good. According to the Bekasi Education observer, Tengku Imam Kobul Moh Yahya (2019). The purpose of planning for Islamic boarding schools is to improve adequate facilities to improve the quality of Islamic education, especially in Bekasi Regency. In this plan, the concept describes the education system in the pesantren that will be built, namely a modern Islamic boarding school but does not leave the traditional values of the pesantren. Neo- Vernacular architecture itself is a blend of modern architectural styles with traditional architectural styles. Because for a modern era like today, many traditional values are gradually fading away. Keywords : Islamic Education, Modern Islamic Boarding School, Bekasi Regency, Neo- Vernacular Architecture